Glucocorticoids and antimalarials in systemic lupus erythematosus: an update and future directions. Issue 5 (September 2018) - Ugarte, Amaia; Danza, Alvaro; Ruiz-Irastorza, Guillermo
Abstract : Purpose of review: The purpose of this review is highlighting the most recent evidence on the clinical efficacy and toxicity of glucocorticoids and antimalarials in systemic lupus erythematosus (SLE) and provide recommendations on their current use. Recent findings: Glucocorticoid toxicity is well known. Recent data confirm the increased risk of infection and damage accrual. An observational study form Hong Kong has seen increased mortality among users of high-dose prednisone regimes. Several studies support the efficacy of medium-low doses and methyl-prednisolone pulses in lupus patients, both with and without nephritis. New data confirm the effects of antimalarials in preventing SLE activity, damage and infections, and in decreasing mortality. New screening recommendations for hydroxychloroquine maculopathy have been recently published. Combining mepacrine and hydroxychloroquine in patients with refractory cutaneous and/or articular lupus activity has proved highly effective. Summary: Universal therapy with hydroxychloroquine should be aimed to patients with SLE without contraindications. Doses greater than 4 mg/kg/day should be avoided and regular eye screening warranted to minimize the risk of macular toxicity. Every effort should be made to reduce the dose of oral glucocorticoids. In moderate-severe flares, pulse methyl-prednisolone are more effective and much less toxic than increasing the oral doses of prednisone.